Raising rangelands and pastoralists to the fore: CGIAR Research Initiative on Livestock and Climate Engagements at the 2024 UNCCD COP16, Riyadh, Saudi Arabia - Flintan, Fiona E.; Onyango, Polycarp; Louhaichi, Mounir; Nanteza, P. (CGIAR System Organization, 2024)
The United Nations Convention to Combat Desertification in Those Countries Experiencing Serious Drought and Desertification, particularly in Africa (UNCCD) is a convention to combat desertification and mitigate the effects of drought through national action programmes that incorporate long-term strategies supported by international cooperation and partnership arrangements. Between 2–13 December 2024, the 16th Convention of the Parties (COP16) was held in Riyadh, Saudi Arabia. Many anticipated that a decision on drought would be a key outcome at this COP. However, despite two weeks of intense negotiations, there remained a lack of agreement on whether to negotiate a framework or a legally binding protocol for addressing drought worldwide. A major milestone was achieved with the launch of the Riyadh Global Drought Resilience Partnership, which had received over USD 12 billion in pledges by the end of COP 16. Decisions on agriculture and rangelands, which are new issues on the UNCCD agenda, also emerged and will shape future discussions and the importance of the convention by bringing agriculture ministries, farmers and pastoralists to the table and expanding the convention’s scope. This report details the engagements of the CGIAR Research Initiative on Livestock and Climate and partners at the UNCCD COP16, including our role in influencing the outcomes, particularly on rangelands.